Multiple Incoherent Deconvolutions for Improving the Image Resolution of Diffraction‐Limited Imaging Systems - Jawahar Prabhakar Desai; Vijayakumar Anand; Joseph Rosen (Advanced Photonics Research)
A new method of imaging with enhanced resolution beyond the diffraction limit is proposed and demonstrated. The target is imaged multiple times, each time with a different phase mask on the aperture of the imaging system. Nonlinear Wiener deconvolution (NWD) reconstructs each image according to the corresponding aperture, and as a result, an image of the target with improved resolution is obtained. The relatively high noise level of each resulting image is eliminated by averaging the multiple deconvolution results. NWD is compared to linear Wiener deconvolution with and without different phase masks. System users can tune the number of imaging events as a tradeoff between low noise and high resolution and between low noise and a low number of camera shots.